Whole Genome Sequence Analysis of a Mycobacterium iranicum, a Newly Identified Non-Tuberculosis Mycobacteria, Strain SBH312 Isolated in Sabah, Malaysia - Jaeyres Jani; Kai Ling Chin; Zainal Arifin Mustapha (Penerbit UMS, 2023)
In 2021, tuberculosis (TB) incidence partially rebounded but remained 12% lower compared with 2019, in which 10 million new TB cases have been reported worldwide. In Malaysia, 20 – 30% of the total TB cases were reported in Sabah. In this communication, we are reporting the whole genome sequence of Mycobacterium iranicum strain SBH312, isolated from a 49-year-old male suffering from a pulmonary infection. This is the first report of M. iranicum, non-tuberculous mycobacteria infecting humans, from Sabah, state of Malaysia. Phylogenetic analysis showed that the M. iranicum strain SBH312 was closely related to strains from Iran and Peninsular Malaysia.